IoT çözümlerinin benzetiminde kullanilan yazilim araçlarinin incelenmesi - Polat, Berna; Das, Resul (Institute of Electrical and Electronics Engineers Inc., 2019)
Internet-based digital transformation process of world countries is increasing rapidly. With the spread of the Internet, IoT-based technological solutions continue to increase in this process. Academic and commercial studies on internet based solutions are increasing day by day. Supply of physical equipment, implementation of applications and obtaining results are not very easy and cheap. Therefore, simulation platforms are used for IoT solutions developed for different workspaces and applications. In this paper, some preferred simulation tools for IoT solutions and application areas are examined and a comparative analysis of these tools is given. © 2019 IEEE.
2019 International Conference on Artificial Intelligence and Data Processing Symposium, IDAP 2019 -- 21 September 2019 through 22 September 2019 -- Malatya -- 153040
Keywords: IoT simulasyon araçlari; IoT çözümleri; Nesnelerin interneti